Patogenesis dan diagnosis immune reconstitution inflammatory syndrome tuberculosis - Gede Wira Mahadita; I Ketut Agus Somia (Intisari Sains Medis, 2020)
Progressive increase in the incidence of tuberculosis (TB) and its coinfection with human immunodeficiency virus (HIV) is observed. Immune system restoration related to highly active antiretroviral therapy (HAART) can cause an immunopathologic reaction termed immune reconstitution inflammatory syndrome (IRIS)-TB. Many aspects of the IRIS phenomenon remain unraveled since its first discovery in 1954. This review is intended to summarize available evidence on various aspects of IRIS with particular focus on its pathogenesis and diagnosis. Insiden tuberkulosis (TB) dan koinfeksinya dengan infeksi human immunodeficiency virus (HIV) terus meningkat dari tahun ke tahun. Perbaikan imunitas yang berhubungan dengan highly active antiretroviral therapy (HAART) dapat disertai dengan reaksi imunopatologis yang disebut sebagai immune reconstitution inflammatory syndrome (IRIS)-TB. Perkembangan pengetahuan mengenai IRIS sejak fenomena ini pertama kali ditemukan pada tahun 1954 masih belum sempurna. Tinjauan ini bertujuan untuk merangkum literatur yang tersedia mengenai beragam aspek IRIS dengan fokus pada aspek patogenesis dan diagnosis.